Going green: survey of perceptions and intentions among Malaysian consumers - Rezai, Golnaz; Phuah, Kit Teng; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (Canadian Research & Development Center of Sciences and Cultures, 2013)
The movement of going green is getting more popular since consumers are increasingly aware about environmental issues and are starting to alter their purchasing behavior to a more environmentally friendly way. Thus, the objective of this study is to investigate Malaysian consumers’ perceptions and intentions towards going green. Descriptive statistics, independent t-test analysis and a binary logistic model were used to analyze the data. The results show that socio-demographic variables such as education levels and age have a significant effect on consumers’ perceptions as well as their attitude towards going green and becoming environmentally friendly. The results also show that subjective norms (environmentalists and the green society) are important determinants of consumers’ intention to go green.